TENDENCIES IN FORMING SHEET METAL PARTS USING INCREMENTAL FORMING ADVANCED TECHNOLOGIES - CATALINA CIOFU; BOGDAN CHIRITA; ROXANA LUPU; COSMIN GRIGORAS; CRINA RADU; GHEORGHE BRABIE (Journal of Engineering Studies and Research)
Stretch forming of sheet metal materials is a highly required process in aerospace industry for manufacturing skin parts. Automation of some processes such as cutting, punching, forming, shearing and nesting in conventional manufacturing tends to combine these forming methods. Some researches are made on the formability of sheet metal materials obtained in incremental forming process with stretch forming and water jet incremental micro-forming with supporting dies. This paper is an attempt to review the newly researches made on optimization of manufacturing metal skin parts to achieve geometrical accuracy.